Heating at the Nanoscale through Drug‐Delivery Devices: Fabrication and Synergic Effects in Cancer Treatment with Nanoparticles. Issue 9 (7th May 2018) - Guisasola, Eduardo; Baeza, Alejandro; Asín, Laura; de la Fuente, Jesús M.; Vallet‐Regí, María
Abstract: Nanocarriers for cancer therapy have been extensively studied, but there is still some research that must be addressed in order to achieve their safe application. In this field, hyperthermia thermal treatments mediated by the use of responsive nanomaterials are not different, and researchers have carried out many attempts to overcome their drawbacks due to the valuable potential of these techniques. Here, an overview is presented of nanodevices based on magnetic‐ and photoresponsive nanocrystals that respond to magnetic fields and/or near‐infrared stimuli for cancer therapies. Special attention is given to the synergic effect that can be achieved with nanoscale heating in combination with chemotherapy through drug‐delivery devices to effectively kill cancer cells. In this way, the nanoparticles act as heating sources or "hot spots, " which can trigger cellular responses in the absence of a global temperature rise, making the tumor cells more sensitive to chemotherapeutics. The fabrication of optical and magnetic drug‐delivery devices, the heating mechanisms, and their applications in tumor treatment are also summarized. Abstract : Nanoparticles acting as "hot spots" can achieve both killing of cancer cells and triggering thermoresponsive drug‐delivery devices without a global temperature rise. The synthesis, heating mechanisms, and applications are discussed along with the synergic effect of nanoscale hyperthermia and chemotherapy, which can be done with these sorts of devices.